PV Power Generation for an Agricultural Load (International Journal of Innovative Research in Computer Science & Technology, 2022)
India is the 6th largest economy of the  world. As per the data 49% of manpower is employed in  farming, where as the farming sector contribution to the GDP  is merely 16%. This is because of two main causes one is the  disguised employment in the farming sector. The second  reason being India’s large portion of farming activities  depend upon the monsoon. The changing weather pattern  makes the corps production vulnerable. The security of crops  can be provided by providing cost effective and continuous  irrigation facilities, which will not only eliminate the  dependency on the weather also help farmers to boost their  economy by increasing the crops production. This might help  to increase the socio-economic condition of the farmers. In  this study, standalone solar PV is introduced and examined  for the said reason. This technology involving renewable  energy provides a novel solution for the challenging task  because during sunny hour maximum water needs to irrigate  the field, and during rainy season the water requirement is null or less. During both the seasons the model can work  effectively, to provide cost effective and eco-friendly energy  supply. The system is modeled and analyzed through  HOMER.
Keywords: PV; Renewable energy; HOMER; Eco friendly; Economic